Dynamics of Nutrient Contents (Phosphorus, Nitrogen) in Water, Sediment and Plants After Restoration of Connectivity in Side‐Channels of the River Rhine. Issue 2 (5th July 2012) - Meyer, Albin; Combroux, Isabelle; Trémolières, Michèle
Abstract During the last century, canalization of the Rhine river led to disconnection of side‐arms, over‐sedimentation of these channels, loss of the fluvial dynamics, and aquatic vegetation change or disappearance. Recent restoration projects aim to reconnect disconnected arms to the main channel. The objective of this study was to assess the nutrient dynamics in restored channels during the vegetation colonization process. In spring, summer, and autumn 2009, the phosphorus and nitrogen contents were measured in water, sediment, and plants, sampled in six channels, two reference sites and four restored ones at different dates. Aquatic vegetation was monitored during the same period. Sites were mesotrophic related to the water nutrient concentrations. However, vegetation communities indicated a eutrophic level, as they were dominated by species like Elodea nuttallii, Myriophyllum spicatum, and Potamogeton perfoliatus. Sites were discriminated by P content and mineral nitrogen in the sediment. We showed an effect of species and season on the plant nutrient content, but there was no relationship between plant nutrient content and nutrients in water and sediment. A negative correlation between mean N plant content and the cover of each species was found. Vegetation characteristics (species richness and cover) and bioavailable phosphorus in the sediment were also correlated. In the restored side‐arms of the river Rhine, phosphorus‐rich sediment seems to be important in the recolonization dynamics, as it was linked to higher species richness, whereas nitrogen played a role in the colonization patterns as a growth limiting factor.